An improved imperceptibility and robustness of 4×4 DCT-SVD image watermarking using modified entropy - Ernawan, Ferda; Ramalingam, Mritha; Sadiq, Ali Safa; Zuriani, Mustaffa (Universiti Teknikal Malaysia Melaka (UTeM), 2017)
A digital protection against unauthorized distribution of digital multimedia is highly on demand. Digital watermarking is a defence in multimedia protection for authorized ownership. This paper proposes an improved watermarking based on 4×4 DCT-SVD blocks using modified entropy in image watermarking. A modified entropy is used to select unnoticeable blocks. The proposed watermarking scheme utilizes the lowest entropy values to determine unnoticeable regions of the watermarked image. This paper investigates the relationship between U(2,1) and U(3,1) coefficients of the U matrix 4×4 DCT-SVD in image watermarking. The proposed watermarking scheme produces a great level of robustness and imperceptibility of the watermarked image against different attacks. The proposed scheme shows the improvement in terms of structural similarity index and normalized correlation of the watermarked image.